2016
DOI: 10.2196/jmir.5790
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Evidence From Systematic Reviews, Qualitative Research, and Expert Knowledge Using Co-Design Techniques to Develop a Web-Based Intervention for People in the Retirement Transition

Abstract: BackgroundIntegrating stakeholder involvement in complex health intervention design maximizes acceptability and potential effectiveness. However, there is little methodological guidance about how to integrate evidence systematically from various sources in this process. Scientific evidence derived from different approaches can be difficult to integrate and the problem is compounded when attempting to include diverse, subjective input from stakeholders.ObjectiveThe intent of the study was to describe and apprai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
105
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(116 citation statements)
references
References 68 publications
1
105
0
Order By: Relevance
“…A review of web‐based interventions for carers across various chronic illnesses found positive changes in psychological health, knowledge, and relationships; however, much of the quality of these studies were deemed as methodologically weak, and therefore more work on the subject is needed . It is argued that the best way to ensure that interventions meet the needs of the target population is to involve stakeholders in design and development . This process known as co‐design has the potential to increase intervention effectiveness …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A review of web‐based interventions for carers across various chronic illnesses found positive changes in psychological health, knowledge, and relationships; however, much of the quality of these studies were deemed as methodologically weak, and therefore more work on the subject is needed . It is argued that the best way to ensure that interventions meet the needs of the target population is to involve stakeholders in design and development . This process known as co‐design has the potential to increase intervention effectiveness …”
Section: Introductionmentioning
confidence: 99%
“…It is argued that the best way to ensure that interventions meet the needs of the target population is to involve stakeholders in design and development . This process known as co‐design has the potential to increase intervention effectiveness …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, during the development process, it might be necessary to conduct additional (unplanned) studies to decide on the exact website components. Overall, involving all parties in the process as co-designers is desirable, as this is more likely to result in a feasible and usable end product (O'Brien et al, 2016;Oudshoorn, Rommes, & Stienstra, 2004).…”
Section: Reflection Practical Tips and Guidelinesmentioning
confidence: 99%